p=3 !
28
-2p-18
Without prior knowledge of the value of q or r, it is impossible to calculate the answer to this equation.
p2 + 2pq + q2 = 1q2 + 2pq + (p2 - 1) = 0q = 1/2 [ -2p plus or minus sqrt( 4p2 - 4p2 + 4 ) ]q = -1 - pq = 1 - p
If: 2p+5r = q Then: p = (q-5r)/2
It is an expression that can be simplified to: 3p+q
5p-7q
p=3 !
No, it is a binomial. A monomial only has one term. A plus or minus sign creates or separates terms.
28
In algebraic terms, the expression "2p + 3q" represents the sum of two terms: 2 times the variable "p" and 3 times the variable "q." To simplify this expression, you can combine like terms by adding the coefficients of "p" and "q" together. Therefore, the simplified form of "2p + 3q" is typically written as "2p + 3q" as it cannot be further simplified without additional context or values assigned to "p" and "q."
-2p-18
Without prior knowledge of the value of q or r, it is impossible to calculate the answer to this equation.
p2 + 2pq + q2 = 1q2 + 2pq + (p2 - 1) = 0q = 1/2 [ -2p plus or minus sqrt( 4p2 - 4p2 + 4 ) ]q = -1 - pq = 1 - p
If a fraction is equivalent to one-half then the numerator is always half the denominator. Or, the double the numerator is the denominator. So, given any other fraction, p/q, if 2p < q then the fraction < 1/2 if 2p = q then the fraction = 1/2 if 2p > q then the fraction > 1/2
3p+7 = 16+2p 3p-2p = 16-7 p = 9